Level and trend of basic education of children in Bangladesh: 1993-1998 - Nath, Samir Ranjan; Chowdhury, A Mushtaque R. (BRAC Research and Evaluation Division (RED), 2020)
Using data generated through two nationally representative sample surveys, this article explores the trends in the level of basic education of Bangladeshi children. The instrument used for the purpose was based on the Declaration of the WorId Conference on Education for All (WCEF A, Jomtien 1990). The findings reveal that the level of 'basic education' increased very slowly, 26.7 percent in 1993 to 29.6 percent in 1998, less than one percentage point per year. Statistically significant improvement was observed in 'life skills knowledge' and 'writing skills', but not in 'reading' or 'numeracy'. Girls progressed in 'reading', 'writing' and 'life skills' while the boys in 'writing' and 'life skills'. Over the period, the level improved for rural children but decreased for urban children. Bangladesh stands much behind to what was targeted at Jomtien Conference in 1990; it will have to wait until 2093 AD to reach the WCEFA goal. The country has made good progress in increasing the access to primary education but a massive drive is necessary to improve the quality of education.